Rutting and fatigue cracking characteristics of toner-modified asphaltic blends - Rambarran, Shane; Clark, Amy; Mohammed, Sharona; Sangster, Nadine; Maharaj, Rean (Universiti Teknologi MARA, Sarawak, 2026)
The improper disposal of electronic waste, particularly waste toner cartridges, poses significant environmental challenges. This research investigated the application of waste toner powder, specifically the powder extracted from printer cartridges, as a modifier in asphaltic mixes to improve rheological characteristics, including fatigue cracking resistance and rutting resistance. Four (4) waste toners (A, B, C & D) were blended into Trinidad Lake Asphalt (TLA) and Trinidad Petroleum Bitumen (TPB) at concentrations of 0%, 5%, 10%, 15%, and 20%. The samples were analysed using dynamic shear rheology (DSR) testing to assess their mechanical properties. The results indicated that incorporating waste toner significantly improves asphalt's resistance to deformation and fatigue. The highest rutting resistance, G*/sin δ was observed in the 20% Toner B at 2.60 × 105 Pa, while the best fatigue cracking resistance, G*sin δ was found in 5% Toner D at 3.93 × 102 Pa. These findings suggest that waste toner-modified asphalt is a viable, sustainable alternative for road paving applications, contributing to both environmental conservation and infrastructure enhancement.